Analyzing collaboration dynamics in new drug R&D: A case study of two lipid-lowering drugs - Zhang, Nan; Guo, Huaqing; Zhang, Mengchao; Wang, Chen; Tian, Ruonan; Shi, Yan; Duan, Zhiguang (Frontiers in Pharmacology, 2025)
IntroductionThe advancements in biotechnology have ushered in a new age for drug development, characterized by increased collaborative efforts. Academic institutions, pharmaceutical firms, hospitals, foundations, and various other entities across different sectors are now joining forces more frequently to accelerate new drug innovation. However, there remains a limited understanding of how scientific and technological advancements are influencing these research collaborations.MethodsIn this study, the development of two types of lipid-lowering drugs served as case studies. A detailed network analysis was performed at the levels of authors, institutions, and countries to quantify the evolutionary trends in research collaboration.ResultsIn the clinical research segment of the academic chain, papers resulting from collaborations tend to receive a higher citation count compared to other areas. However, there were notably fewer collaborative connections between authors transitioning from basic to developmental research and beyond. Collaboration models involving universities with enterprises, hospitals, or both are becoming more prevalent in biologics R&D. These models demonstrate effects of similarity and proximity. Additionally, there has been an increase in the involvement of developing countries in the research and development of new biologic drugs on a national and regional scale.ConclusionNew drug R&D research collaboration patterns evolve spontaneously with productivity updates. In the future, it is necessary to enhance the involvement of pharmaceutical companies in the basic research phase of new drug development, continuously strengthen the relationships across all segments of the academic chain, and thoroughly boost the efficiency of transforming new drug R&D into practical applications.